2007
DOI: 10.1002/anie.200701935
|View full text |Cite
|
Sign up to set email alerts
|

Massadine Chloride: A Biosynthetic Precursor of Massadine and Stylissadine

Abstract: In this Communication, the structure of compounds 3 and 5 was incorrectly drawn. The correct structure is shown below. The editorial office apologizes for this oversight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 25 publications
(15 reference statements)
2
46
0
Order By: Relevance
“…Indeed, the pathway from one to the other may not be simple, but by postulating the biosynthetic relationships, a viable intermediate that may be a natural product in its own right can be identified. For example, when massadine chloride was isolated 52 , it had previously been predicted as a key biosynthetic intermediate in the synthesis of the pyrrole-imidazole alkaloid family of natural products (as described below) 53 In three consecutive reports published in 2007, the structures of notoamides A-D (isolated from the marine fungus Aspergillus sp.,) were revealed, along with the biomimetic syntheses of notoamides B-D [54][55][56] . Subsequently, the structures of up to 20 members of this family-derived from isoprene, tryptophan and proline (Fig.…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the pathway from one to the other may not be simple, but by postulating the biosynthetic relationships, a viable intermediate that may be a natural product in its own right can be identified. For example, when massadine chloride was isolated 52 , it had previously been predicted as a key biosynthetic intermediate in the synthesis of the pyrrole-imidazole alkaloid family of natural products (as described below) 53 In three consecutive reports published in 2007, the structures of notoamides A-D (isolated from the marine fungus Aspergillus sp.,) were revealed, along with the biomimetic syntheses of notoamides B-D [54][55][56] . Subsequently, the structures of up to 20 members of this family-derived from isoprene, tryptophan and proline (Fig.…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 98%
“…Another recent example of natural product discovery is exiguamine B (52). Exiguamine A (50), first isolated from the marine sponge Neopetrosia exigua, is a hexacyclic alkaloid and the most potent inhibitor of the enzyme indoleamine 2,3-dioxygenase (IDO) known 71 .…”
Section: Overturning Chemical 'Rules'mentioning
confidence: 99%
“…Substitution of the secondary hydroxyl group with chloride with stereoretention proceeded by exploiting a neighboring group effect with the guanidine containing F ring. Secondary alcohol activation using sulfuryl chloride induced the participation of guanidine depicted in 33 analogous to massadine aziridine , 18 and subsequent nucleophilic attack of chloride afforded 34 with the α con guration of chloride, along with a small amount of the epimer at the C20 position in the unnatural con guration. On the other hand, the hemiaminal hydroxyl group also reacted with excess sulfuryl chloride to give a dichloride when more than 1.0 equiv of sulfuryl chloride was used, but the chloride at the C20 position was readily hydrolyzed back to 34 in THF H 2 O at 50 .…”
Section: Total Synthesis Of Palau Aminementioning
confidence: 99%
“…31,40 Cyclization of 14 would afford massadine chloride ( 6b ), axenellamines ( 7 ), and konbu’acidins ( 8b,c ). While massadine ( 6a ) and massadine chloride ( 6b ) could be produced independently, Köck and Baran showed that 6a could be converted to 6b completely by incubating 6a in water at 60 °C for 4 h. 40 The retention of stereochemistry could be explained by an aziridinium intermediate that was previously proposed by Romo. 19d …”
Section: Biosynthetic Hypothesesmentioning
confidence: 99%